(3JfhjQ GdYjhf HESJYeGd GdShGc GdeSfhfs
(3ChdgG (B:s
(3jGeGdc GdCedGc djS ShGc , hjG eMQc GdCadGc gH di QMeI HgG CQGc hHYO abO QZH Edi ef gh YRjR Ydi Cf CLeY dg fHPI dWjaI ai CMcGe GdeShGc hahGFO GdShGc aCLHJg hSejJgG hJfMUQ ai CQHYI CHhGH s
(3BNQgG (B:s
(3Ke bGd GdeCehf hgh Wad cja bGd Sc bGd bGd CejQ GdeDefjf gcPG adjcf BOGH GdNWGH s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdahGJM hGdahGUd HGdMeQIs
(3HChdgG aGFOI Ydi bhdg JYGdi hefge ef jSJeYhf Edjc ai ShQI jhfSs
(3HBNQgG hbag cGJH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3Gdabg GdESdGejs